Evaluación del desempeño de las variables del comportamiento organizacional en Majestad Tv de la provincia Santo Domingo de los Tsáchilas. - Moreira Sabando, Diana Carolina (2018)
Currently there are several audiovisual companies in Ecuador with difficulties in their growth, based on this problem arises research of evaluate the performance of the variables of organizational behavior of enterprise Majesty TV in Santo Domingo the Tsachilas province, the methodology used research was the qualitative-quantitative where main methods were used as the experts those who valued variables and classics as the inductive emphasizing the direction that was considered in the study, the deductive helped to discover the shortcomings that were affecting the behaviour and the descriptive, it is used to measure and also specify the results of the different variables, techniques such as observation, interview, survey, characterization of variables, Delphi, kendall among others, for the analysis of reliability of work were established three tools the (RIR) relative interquartile range, the Alpha of Cronbach and the level of consensus, according to the result your procedure, it began with the search for the variables, then laid down and approved by experts on issues of organizational behavior for their respective implementation, used in surveys targeting partners where identified that there are weaknesses within the company generated by both individual and group behavior, these errors must be corrected by the owner and because of this the research team proposes a program of improvements with its respective prioritization so you impel both the performance of the workers such as the development of the entity.